Palm oil for connoisseurs - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2003)
There s a premium market in Abidjan, Côte d Ivoire for traditionally produced red palm oil prices are double for oil from natural plantations.